Microbial eukaryotes and their functional importance in the Arctic. A Svalbardian perspective - Wutkowska, Magdalena (UiT The Arctic University of Norway, 2020)
Microbial eukaryotes, including protists and fungi, play diverse functions in virtually all ecosystems. In the High Arctic, their high biomass and diversity reflects crucial ecological importance and the performance of key ecological processes. Protists are the main primary producers in arctic seas, whereas fungi are an important group of decomposers and symbiotic partners of plants in terrestrial habitats. During the last decade, along with the development of new high-throughput sequencing methods, our knowledge regarding arctic microbial eukaryotes has expanded. Previous studies have identified the major groups of microbial eukaryotes present in Svalbard and how their richness and abundance may vary along various temporal and spatial scales. Those studies used high-throughput sequencing to reveal the dynamics, biodiversity patterns and community composition of diverse microbial eukaryotes such as marine protists, soil and root-associated fungi. However, altogether these studies have just scratched the surface of disentangling the biodiversity and its drivers. Basic questions regarding taxonomic diversity, community composition and their drivers are addressed in a limited manner, often leaving most of the observed variation unexplained. Regarding functionality of these organisms, even less is known. At the same time, these findings have also increased the amount of questions about microbial eukaryotes, their life histories, strategies, seasonality, sensitivity to changes in environmental conditions, as well as functional importance of these organisms at different scales. Previously unexplained variation and other emerging knowledge gaps regarding microbial eukaryotes formed a backstage for this thesis. The main focus was to look at these organisms from a functional angle regarding variation related to methodology, seasonality and biotic factors through case studies addressing the following knowledge gaps. Firstly, to understand the functionality of biodiversity in a temporal and spatial context of cold soils, ...